Learning Media Innovation: Lift the Flap Book Digital in Increasing Interest in Learning Science for Third-Grade Elementary School Students - Bintoro, Totok; Fahrurrozi; Ika Lestari; Febriani Rofiqoh (Jurnal Penelitian dan Pengembangan Pendidikan, 2022)
The The COVID-19 pandemic in Indonesia impacts all sectors, including the education sector. This pandemic has changed the use of face-to-face learning systems to online or distance learning. In this distance learning system, teachers are required to deliver learning materials well and pleasantly to students. This study aims to develop lift the flap book digital media to increase student interest in learning during the pandemic. This type of research is developed using the ADDIE method. The population of this study amounted to 24 students. The method used in data collection is observation, interviews, and questionnaires. The instrument used in data collection is a questionnaire sheet. The data analysis technique used to analyze the research data is descriptive qualitative and quantitative. The result of the analysis is that Lift The Flap Book's digital media received very good qualifications from experts to be suitable for use in learning. It was concluded that the media was very suitable for increasing the learning interest of third-grade elementary school students during the pandemic.